Indirect positive evidence in the acquisition of a subset grammar. (3rd July 2017) - Schwartz, Misha; Goad, Heather
ABSTRACT: This article proposes that second language learners can use indirect positive evidence (IPE) to acquire a phonological grammar that is a subset of their L1 grammar. IPE is evidence from errors in the learner's L1 made by native speakers of the learner's L2. It has been assumed that subset grammars may be acquired using direct or indirect negative evidence or, in certain L1–L2 combinations, using direct positive evidence. The utility of IPE is tested by providing native speakers of English with indirect evidence of the phonotactic constraints holding of word-initial clusters in Brazilian Portuguese (BP), which are a subset of those in English. Participants were tested on the well-formedness of BP-like words, and the results indicate that approximately one-third were able to use the IPE to make appropriate BP-like judgments. This suggests that IPE may be another source of evidence that learners can use to build a grammar that is a subset of their own L1 grammar.